(3eQGJY GdZRdGf aj hUa GdMSGf ef GdZdeGfs - (3eMeO Hf MSf Hf Ydj Hf YKeGf GdfhGLj GdTGaYj , TeS GdOjf,J (B859 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO ddg GdPj Ndb GdEfSGf aj CMSf Jbhje abO SCdfj HYV GdENhGf Cf CLeY dg ofHPI aj GdMSGf ef GdZdeGf s
(3BNQgG (B:s
(3bdJ(B: (3hdh bGd(B: (3dh de Jcf QhVI ddMSf Ch adcG eG cGf LeY ajc GdYUf hGdbeQ dcGf CHdZ aj GdeYfi Je eQGJY GdZRdGfhGdMeO ddg hMOg s
(3GfXQ GdLRA GdChd Qbe (B756 (3COHs
(3QJHg Ydi NeSI CHhGHs
(3UaMI GdYfhGf eRNQaIs
(3hHgG BKGQ WeS cKjQ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdCOHs